1981
DOI: 10.1677/joe.0.0910457
|View full text |Cite
|
Sign up to set email alerts
|

Rise in Plasma Concentration of Aldosterone During Long-Term Angiotensin Ii Suppression

Abstract: The plasma concentration of aldosterone was followed in seven hypertensive patients before and during long-term angiotensin II suppression with the orally active angiotensin-I-converting-enzyme inhibitor, captopril. The plasma concentration of aldosterone decreased initially from 74 to 21 pg/ml (P less than 0.05) after 1 month of administration of captopril. Thereafter the plasma concentration of aldosterone began to rise and after 1 year reached a level of 165 pg/ml. During long-term captopril therapy the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
152
0
7

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(160 citation statements)
references
References 31 publications
1
152
0
7
Order By: Relevance
“…1 Although ACE-I might be expected to reduce aldosterone levels by reducing the stimulating effect of angiotensin II on aldosterone production, recent studies have demonstrated that neither angiotensin II nor aldosterone plasma levels are suppressed chronically by clinically prescribed doses of ACE-I. 2,3 Aldosterone has been implicated as a contributor to structural remodeling of the left ventricle, 4 -6 and the beneficial effects of spironolactone on mortality have been attributed to inhibition of the collagen-generating influence of aldosterone. 7,8 Aldosterone secretion is stimulated by several factors in addition to angiotensin II, and these alternate mechanisms may be important determinants of aldosterone production and its levels in the plasma and tissues in patients with HF.…”
mentioning
confidence: 99%
“…1 Although ACE-I might be expected to reduce aldosterone levels by reducing the stimulating effect of angiotensin II on aldosterone production, recent studies have demonstrated that neither angiotensin II nor aldosterone plasma levels are suppressed chronically by clinically prescribed doses of ACE-I. 2,3 Aldosterone has been implicated as a contributor to structural remodeling of the left ventricle, 4 -6 and the beneficial effects of spironolactone on mortality have been attributed to inhibition of the collagen-generating influence of aldosterone. 7,8 Aldosterone secretion is stimulated by several factors in addition to angiotensin II, and these alternate mechanisms may be important determinants of aldosterone production and its levels in the plasma and tissues in patients with HF.…”
mentioning
confidence: 99%
“…[20][21][22] ALD breakthrough generally occurs in about half of the cases within 12 months. 23,24 Recently, ALD breakthrough was observed in 23% of hypertensive patients during candesartan treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This unfortunately is not the case. Several investigators have demonstrated that the use of ACEinhibitors initially causes an acute decrease in the concentration of aldosterone, but with continued use, this suppression is not sustained (59)(60)(61)(62).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%